Preparation method and application of nickel-based electrocatalyst rich in multi-vacancy defects

The nickel-based catalyst is synthesized and electrochemically reconstituted in situ by hydrothermal method, and the problem of low catalytic efficiency of 5-hydroxymethylfurfural oxidation in the prior art is solved, and an efficient, stable and economical catalytic effect is achieved.

CN119710806AActive Publication Date: 2025-03-28NORTHEAST FORESTRY UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411893139.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently catalyze the oxidation of 5-hydroxymethylfurfural, and traditional chemical oxidation methods have problems such as toxicity, high cost and yield limitations.

Method used

Metal-doped nickel-based catalyst precursors containing anionic vacancies were synthesized by a one-step hydrothermal method, and a nickel-based hydroxide/oxide catalyst rich in multi-vacancies were obtained by electrochemical in situ reconstruction.

Benefits of technology

It achieves catalytic effect of obtaining higher oxidation capacity at lower potentials, has excellent performance and stability, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710806A_ABST
    Figure CN119710806A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a nickel-based electrocatalyst rich in multi-vacancy defects, and the preparation method comprises the following steps: by taking foamed nickel as a substrate nickel source, metal sodium salt or metal nitrate as a metal precursor and sodium salt as an anion precursor, constructing a high-valence metal doped nickel-based catalyst precursor through a one-step hydrothermal method; on this basis, anion vacancies are regulated and controlled by adopting a hydrogen peroxide etching strategy, then in electrochemical in-situ reconstruction, anions are replaced by hydroxyl in a solution, high-valence metal is leached out to form cation vacancies, and therefore the nickel-based hydroxide / oxide (VM, N-Ni (OxHy)) catalyst with the cation vacancies and the anion vacancies is obtained. The preparation process of the nickel-based electrocatalyst has the characteristics of being simple and easy to operate and control, can be expanded and applied to preparation of other multi-vacancy defect metal hydroxides / oxides, and provides a new thought and method for designing and developing a novel efficient biomass oxidation electrocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a nickel-based electrocatalyst rich in multiple vacancy defects, specifically, firstly synthesizing a metal-doped nickel-based electrocatalyst containing anion vacancies (M-Ni) by a one-step hydrothermal method. x N y -N V ) catalyst precursor, and then the nickel-based hydroxide / oxide (V M,N -Ni(O x H y ))catalyst method. Background Art

[0002] As people use petroleum energy to generate electricity and produce value-added chemicals, the danger of global warming has increased. Therefore, people have begun to pay attention to the development of sustainable clean energy storage and conversion technologies to mitigate the adverse effects of climate change. Biomass is mainly produced by plant photosynthesis and is the only renewable resource that has both energy and raw material properties. The selective conversion of hydrocarbons in biomass into fuels and high-value chemicals provides a green way to minimize our dependence on non-renewable resources. 5-Hydroxymethylfurfural (HMF) is one of the most popular cellulose-derived platform chemicals. It can be oxidized to produce a variety of key chemical products such as synthetic polymer monomers, fine chemicals, drug precursors, fuel additives, and liquid fuels, and has extremely broad development prospects. Among them, 2,5-furandicarboxylic acid (FDCA) is the most valuable product of 5-Hydroxymethylfurfural oxidation and is used as an important monomer for the production of biopolymers to replace petroleum-based polyethylene terephthalate. However, the classical chemical oxidation of organic compounds involves high-valent chromium, manganese, copper oxides, lead salts, active dimethyl sulfoxide, iodine, organic amino oxides, etc. These methods have significant disadvantages, such as being toxic (except for manganese-containing catalysts), or being limited to small-scale reactions due to the use of non-catalytic materials (such as alumina, alumina catalysts) for the oxidation transformation, and being subject to challenges in product yield and separation, thus limiting their industrial-scale industrial application. In sharp contrast, electrochemical energy has emerged as a more efficient alternative and sustainable method that is able to oxidize organic molecules without the need for additional expensive or toxic oxidants. The electrooxidation process can be controlled with high precision in terms of product yield and selectivity by simply adjusting the working potential, electrode materials, cell configuration, electrolyte, etc. In addition, most electrooxidations are carried out at room temperature and atmospheric pressure, which has the significant advantage of reduced energy consumption compared to traditional chemical oxidation methods.

[0003] Nickel-based catalysts (e.g., nickel hydroxide, nickel sulfide, nickel phosphide, nickel boride, etc.) have been shown to be highly efficient catalysts for biomass electrooxidation and have been extensively studied due to their outstanding structures. It is reported that nickel sulfide is doped with molybdenum atoms, and after electrochemical in-situ reconstruction, molybdenum and sulfur atoms are leached out to obtain nickel oxide / nickel hydroxide (V) with metal vacancies. M -NiO x H y ) catalyst, metal vacancies can promote the high-valent Ni 3+ -O active sites are formed, thereby improving the catalytic performance of 5-hydroxymethylfurfural; in addition, the introduction of oxygen vacancies in nickel-iron layered hydroxides can promote the adsorption of 5-hydroxymethylfurfural molecules, which is also beneficial to the oxidation of 5-hydroxymethylfurfural molecules. With the development of defect chemistry, researchers have gradually realized the importance of vacancy defects (metal vacancy defects and oxygen vacancy defects) in heterogeneous catalysis (such as electrocatalysis) based on vacancy-rich nanocatalysts. Studies have shown that in electrochemical processes, nickel-based catalysts with vacancy defects are generally more susceptible to irreversible surface reconstruction in the electrolyte, resulting in nickel oxide / nickel hydroxide (NiO x H y ) species. However, there has been no report on the efficient catalytic oxidation of 5-HMF by multi-vacancy nickel-based catalysts. The research and application of multi-vacancy synergistic promotion of 5-HMF oxidation has not been realized so far, and it has always been a bottleneck.

[0004] In view of the above-mentioned deficiencies, the subject of the present invention is to provide a method for preparing a nickel-based electrocatalyst rich in multi-vacancy defects that can efficiently catalyze the oxidation of 5-hydroxymethylfurfural. Summary of the invention

[0005] The invention solves the problem by overcoming the shortcomings of the prior art and providing a nickel-based hydroxide / oxide catalyst (V M,N -Ni(O x H y )) and used in the oxidation reaction of 5-hydroxymethylfurfural; a metal-doped nickel-based (M-Ni) containing anion vacancies was synthesized by one-step hydrothermal synthesis. x N y -N V ) The method for preparing the catalyst precursor is simple, easy to operate and control, is conducive to large-scale industrial production, and has significant economic and social benefits.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is:

[0007] The present invention first discloses a method for preparing a nickel-based electrocatalyst rich in multi-vacancy defects, comprising the following steps:

[0008] (1) dissolving the metal precursor and the anion precursor in 30 mL of ultrapure water respectively, and dissolving and dispersing them by ultrasonication for 30 min to obtain a first solution;

[0009] (2) placing the nickel foam in the first solution; and using magnetic stirring to completely soak the nickel foam to obtain a second product;

[0010] (3) vertically placing the second product in the inner lining of a closed reactor for hydrothermal reaction, and washing and drying to obtain a third product;

[0011] (4) The third product is placed in a hydrogen peroxide solution and soaked for 60 seconds, followed by washing and drying to obtain a metal-doped nickel-based (M-Ni) x N y -N V ) catalyst precursor;

[0012] (5) Metal-doped nickel-based (M-Ni) x N y -N V )The catalyst precursor is electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide to obtain a nickel-based electrocatalyst rich in multi-vacancy defects.

[0013] Furthermore, the metal precursor in step (1) includes but is not limited to:

[0014] Any one of sodium tungstate dihydrate, sodium molybdate dihydrate, sodium vanadate dodecahydrate, manganese nitrate tetrahydrate, cadmium nitrate nonahydrate, aluminum nitrate nonahydrate, and zinc nitrate hexahydrate;

[0015] The anion precursors include but are not limited to:

[0016] Any one of sodium sulfide nonahydrate, sodium hypophosphite hydrate, and sodium borohydride;

[0017] In the first solution, the purity of the metal precursor and the anion precursor are both above 99.5%, the mass fraction of hydrogen peroxide is 30%±1%, and the nickel foam is commercial nickel foam with a thickness of 1.6 nm.

[0018] Furthermore, in step (1), the molar ratio of anions to metal ions in the first solution is 10:1.

[0019] Furthermore, the nickel foam in step (2) further includes the following treatment before use:

[0020] The nickel foam was cut into 1cm*2cm blocks, and then ultrasonically treated with 3mol / L hydrochloric acid, ultrapure water, anhydrous ethanol and ultrapure water for 15min in sequence. The oxide on the surface of the nickel foam was treated with hydrochloric acid solution, the organic matter on the surface of the nickel foam was treated with anhydrous ethanol, and the surface residue was cleaned with ultrapure water. The treated nickel foam was placed in a vacuum oven and dried at 60°C for 12h.

[0021] Furthermore, the conditions of the hydrothermal reaction in step (3) are: hydrothermal temperature ≥ 160°C, hydrothermal time ≥ 8h; the washing is: ultrasonic washing with ultrapure water for 10 min, washing twice, and ultrasonic washing with anhydrous ethanol for 10 min once, placing the washed product in a vacuum oven and drying it at 60°C for 12h.

[0022] Furthermore, the washing in step (4) includes: ultrasonic washing with ultrapure water twice, ultrasonic washing with anhydrous ethanol once, and each ultrasonic washing time is 10 minutes; the drying condition is: drying at 60°C for 12 hours.

[0023] Furthermore, the electrochemical in-situ reconstruction in step (5) adopts a three-electrode system, including: a working electrode, a reference electrode and a counter electrode; wherein: the working electrode is a metal-doped nickel-based catalyst precursor containing anion vacancies, the reference electrode is mercury / mercury oxide, and the counter electrode is a carbon rod.

[0024] Furthermore, the in-situ reconstruction condition in step (5) is: using cyclic voltammetry, at a potential range of 0.80 V to 1.70 V, at 50 mV s -1 The scanning rate is more than 50 circles.

[0025] The present invention also discloses a nickel-based electrocatalyst rich in multiple vacancy defects and containing multiple vacancy defects, which is prepared according to any of the above-mentioned preparation methods.

[0026] The invention also discloses an application of the nickel-based electrocatalyst rich in multi-vacancy defects in the electro-oxidation reaction process of 5-hydroxymethylfurfural.

[0027] Furthermore, the application includes:

[0028] 63 mg of 5-hydroxymethylfurfural was weighed and dissolved in the anode of an H-type cell containing 10 mL of potassium hydroxide solution, and the cathode also had 10 mL of potassium hydroxide solution; its catalytic performance was investigated by linear sweep voltammetry, electrolysis was performed by constant potential polarization, and HPLC was used to quantitatively detect the conversion rate of 5-hydroxymethylfurfural and the Faraday efficiency of 2,5-furandicarboxylic acid.

[0029] Furthermore, the concentration of the potassium hydroxide solution is 1 mol / L; the linear sweep voltammetry potential range is 0.80V to 1.70V, and the constant potential polarization potential is 1.45V;

[0030] The calculation formulas for the 5-hydroxymethylfurfural conversion rate and the 2,5-furandicarboxylic acid Faraday efficiency are as follows:

[0031] Conversion rate of 5-hydroxymethylfurfural (%) = moles of 5-hydroxymethylfurfural consumed / moles of initial 5-hydroxymethylfurfural×100% Faraday efficiency FE of 2,5-furandicarboxylic acid (%) = charge amount of product / charge amount passed×100%.

[0032] The electron microscopy test results show that after electrochemical in-situ reconstruction, amorphous NiO appears on the catalyst surface. x The thin layers contain rough lattice fringes and local lattice distortions, indicating the presence of a large number of atomic vacancies.

[0033] The advantages of the present invention compared with the prior art are:

[0034] (1) The present invention adopts a one-step hydrothermal method, which is simple, easy to operate and control, is conducive to large-scale industrial production, and has significant economic and social benefits.

[0035] (2) The present invention uses non-precious metal catalysts, has low cost consumption, and is universally applicable.

[0036] (3) The present invention is highly efficient, and the obtained catalyst has excellent performance and can obtain higher oxidation capacity at a lower potential, which is conducive to large-scale application.

[0037] (4) The present invention adopts a strategy of multiple vacancy defects to improve catalyst performance, which is insufficient in existing research and provides ideas for the future design of defective catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The nickel-based hydroxide / oxide (V) rich in multi-vacancy defects after electrochemical in-situ reconstruction obtained in Example 1 W,S -Ni(O x H y ))High-resolution electron microscope photo of the catalyst;

[0039] Figure 2 is a performance comparison diagram of nickel-based hydroxide / oxide catalysts containing different vacancy defects obtained in Examples 1-3 of the present invention;

[0040] Figure 3 The nickel-based hydroxide / oxide (V W,S -Ni(O x H y ))Stability diagram of the catalyst. DETAILED DESCRIPTION

[0041] To further illustrate the present invention, the following specific embodiments are listed, but the scope of the claims of the present invention is not limited by these embodiments. At the same time, the embodiments only provide some conditions for achieving this purpose, but do not mean that these conditions must be met to achieve this purpose. In order to enable people in the technical field to better understand the technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings of the specification and through specific implementation methods.

[0042] Example 1

[0043] 960.7 mg of sodium sulfide nonahydrate and 131.9 mg of sodium tungstate dihydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and hydrothermal was placed in the lining of a closed reactor. The hydrothermal temperature was 160 ° C, the hydrothermal time was 8 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a tungsten-doped nickel-based sulfur-vacancy-containing (W-Ni3S2-S v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V W,S -Ni(O x H y ))Electrocatalyst.

[0044] Figure 1 The nickel-based hydroxide / oxide (V W,S -Ni(O x H y ))High-resolution electron microscope photo of the catalyst. Amorphous NiO appears on the catalyst surface x The thin layers contain rough lattice fringes and local lattice distortions, indicating the presence of a large number of atomic vacancies.

[0045] Example 2

[0046] 960.7 mg of sodium sulfide nonahydrate and 131.9 mg of sodium tungstate dihydrate were dissolved in 30 mL of ultrapure water, respectively, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and hydrothermal was placed in the lining of a closed reactor. The hydrothermal temperature was 160 ° C, the hydrothermal time was 8 h, and then washed and dried to obtain a tungsten-doped nickel-based (W-Ni3S2) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V) containing metal vacancy defects. M -Ni(O x H y ))Electrocatalyst.

[0047] Example 3

[0048] 960.7 mg of sodium sulfide nonahydrate was dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The nickel foam was placed in the solution, and hydrothermal was placed in the lining of a closed reactor at a hydrothermal temperature of 160 ° C for 8 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a nickel-based (Ni3S2-S v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V S -Ni(O x H y ))Electrocatalyst.

[0049] Example 4

[0050] 960.7 mg of sodium sulfide nonahydrate and 96.8 mg of sodium molybdate dihydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The nickel foam was placed in the solution, and the nickel foam was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C. The hydrothermal time was 8 h, and the nickel foam was washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed, and dried to obtain a molybdenum-doped nickel-based (M) containing sulfur vacancies. O -Ni3S2-S v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Mo,S -Ni(O x H y ))Electrocatalyst.

[0051] Example 5

[0052] 960.7 mg of sodium sulfide nonahydrate and 152.0 mg of sodium vanadate dodecahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and the foamed nickel was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 8 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a vanadium-doped nickel-based sulfur-vacancy-containing (V-Ni3S2-S v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V V,S -Ni(O x H y ))Electrocatalyst.

[0053] Example 6

[0054] 960.7 mg of sodium sulfide nonahydrate and 100.4 mg of manganese nitrate tetrahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The nickel foam was placed in the solution, and the foam was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 8 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a manganese-doped nickel-based material containing sulfur vacancies (Mn-Ni3S2-S v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Mn,S -Ni(O x H y ))Electrocatalyst.

[0055] Example 7

[0056] 960.7 mg of sodium sulfide nonahydrate and 160.1 mg of cadmium nitrate nonahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and the foamed nickel was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 8 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a chromium-doped nickel-based sulfur-vacancy-containing (Cr-Ni3S2-S v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Cr,S -Ni(O x H y ))Electrocatalyst.

[0057] Example 8

[0058] 960.7 mg of sodium sulfide nonahydrate and 150.1 mg of aluminum nitrate nonahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and hydrothermal was placed in the lining of a closed reactor. The hydrothermal temperature was 160 ° C, the hydrothermal time was 8 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain an aluminum-doped nickel-based (Al-Ni3S2-S v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Al,S -Ni(O x H y ))Electrocatalyst.

[0059] Example 9

[0060] 960.7 mg of sodium sulfide nonahydrate and 128.9 mg of zinc nitrate hexahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The nickel foam was placed in the solution, and the foam was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 8 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a zinc-doped nickel-based sulfur-vacancy-containing (Zn-Ni3S2-S v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Zn,S -Ni(O x H y ))Electrocatalyst.

[0061] Example 10

[0062] 351.9 mg of sodium hypophosphite dihydrate and 131.9 mg of sodium tungstate dihydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and hydrothermal was placed in the lining of a closed reactor. The hydrothermal temperature was 160 ° C, the hydrothermal time was 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a tungsten-doped nickel-based (W-Ni2P-P v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V W,P -Ni(O x H y ))Electrocatalyst.

[0063] Embodiment 11

[0064] 351.9 mg of sodium hypophosphite dihydrate and 96.8 mg of sodium molybdate dihydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and hydrothermal was placed in the liner of a closed reactor. The hydrothermal temperature was 160 ° C, the hydrothermal time was 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a molybdenum-doped nickel-based (Mo-Ni2P-P v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Mo,P -Ni(O x H y ))Electrocatalyst.

[0065] Example 12

[0066] 351.9 mg of sodium hypophosphite dihydrate and 152.0 mg of sodium vanadate dodecahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and the foamed nickel was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a vanadium-doped nickel-based (V-Ni2P-P v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V V,P -Ni(O x H y ))Electrocatalyst.

[0067] Embodiment 13

[0068] 351.9 mg of sodium hypophosphite dihydrate and 100.4 mg of manganese nitrate tetrahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and hydrothermal was placed in the lining of a closed reactor. The hydrothermal temperature was 160 ° C, the hydrothermal time was 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a manganese-doped nickel-based (Mn-Ni2P-P v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Mo,P -Ni(O x H y ))Electrocatalyst.

[0069] Embodiment 14

[0070] 351.9 mg of sodium hypophosphite dihydrate and 160.1 mg of cadmium nitrate nonahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and hydrothermal was placed in the lining of a closed reactor. The hydrothermal temperature was 160 ° C, the hydrothermal time was 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a chromium-doped nickel-based (Cr-Ni2P-P v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Cr,P -Ni(O x H y ))Electrocatalyst.

[0071] Embodiment 15

[0072] 351.9 mg of sodium hypophosphite dihydrate and 150.1 mg of aluminum nitrate nonahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The nickel foam was placed in the solution, and the foam was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain an aluminum-doped nickel-based material containing phosphorus vacancies (Al-Ni2P-P v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Al,P -Ni(O x H y ))Electrocatalyst.

[0073] Example 16

[0074] 351.9 mg of sodium hypophosphite dihydrate and 128.9 mg of zinc nitrate hexahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The nickel foam was placed in the solution, and the foam was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed, and dried to obtain a zinc-doped nickel-based structure containing phosphorus vacancies (Zn-Ni2P-P v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Zn,P -Ni(O x H y ))Electrocatalyst.

[0075] Embodiment 17

[0076] 148.1 mg of sodium borohydride and 131.9 mg of sodium tungstate dihydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and hydrothermal was placed in the liner of a closed reactor. The hydrothermal temperature was 160 ° C, the hydrothermal time was 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a tungsten-doped nickel-based (W-NiB x -B v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V W,B -Ni(O x H y ))Electrocatalyst.

[0077] Embodiment 18

[0078] 148.1 mg of sodium borohydride and 96.8 mg of sodium molybdate dihydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and hydrothermal was placed in the lining of a closed reactor. The hydrothermal temperature was 160 ° C, the hydrothermal time was 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a molybdenum-doped nickel-based (Mo-NiB x -B v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Mo,B -Ni(O x H y ))Electrocatalyst.

[0079] Embodiment 19

[0080] 148.1 mg of sodium borohydride and 152.0 mg of sodium vanadate dodecahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and the foamed nickel was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a vanadium-doped nickel-based (V-NiB x -B v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V V,B -Ni(O x H y ))Electrocatalyst.

[0081] Embodiment 20

[0082] 148.1 mg of sodium borohydride and 100.4 mg of manganese nitrate tetrahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and hydrothermal was placed in the lining of a closed reactor. The hydrothermal temperature was 160 ° C, the hydrothermal time was 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a manganese-doped nickel-based (Mn-NiB x -B v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Mn,B -Ni(O x Hy ))Electrocatalyst.

[0083] Embodiment 21

[0084] 148.1 mg of sodium borohydride and 160.1 mg of cadmium nitrate nonahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and the foamed nickel was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a chromium-doped nickel-based structure containing boron vacancies (Cr-NiB x -B v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Cr,B -Ni(O x H y ))Electrocatalyst.

[0085] Embodiment 22

[0086] 148.1 mg of sodium borohydride and 150.1 mg of aluminum nitrate nonahydrate were dissolved in 30 mL of ultrapure water, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and the foamed nickel was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain an aluminum-doped nickel-based structure containing boron vacancies (Al-NiB x -B v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (V Al,B -Ni(O x H y ))Electrocatalyst.

[0087] Embodiment 23

[0088] 148.1 mg of sodium borohydride and 128.9 mg of zinc nitrate hexahydrate were dissolved in 30 mL of ultrapure water, respectively, and ultrasonically dissolved and dispersed by an ultrasonic machine. The foamed nickel was placed in the solution, and the foamed nickel was placed in the lining of a closed reactor for hydrothermal treatment at a temperature of 160 ° C for 12 h, and then washed and dried. The product was placed in a hydrogen peroxide solution for 60 s, washed and dried to obtain a zinc-doped nickel-based structure containing boron vacancies (Zn-NiB x -B v ) catalyst precursor, which was electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide solution to obtain a nickel-based hydroxide / oxide (VZn,B -Ni(O x H y ))Electrocatalyst.

[0089] Application Examples

[0090] The catalyst obtained in Examples 1-3 was used in the oxidation reaction of 5-hydroxymethylfurfural (HMF) according to the method of the present invention, as follows:

[0091] 63 mg of 5-hydroxymethylfurfural (HMF) was weighed and dissolved in the anode of an H-type cell containing 10 mL of 1 mol / L potassium hydroxide solution (1M KOH), and the cathode also contained 10 mL of 1 mol / L potassium hydroxide solution; a three-electrode system was used, with the working electrode (metal-doped nickel-based (M-Ni) containing anion vacancies) x N y -N V )catalyst precursor), reference electrode (mercury / mercuric oxide), counter electrode (carbon rod), and linear sweep voltammetry were used to investigate its catalytic performance.

[0092] Figure 2 The performance comparison diagram of nickel-based hydroxide / oxide catalysts with different vacancy defects obtained in Examples 1-3 is shown in the figure. As shown in the figure, the catalyst rich in multiple vacancy defects (V W,S -Ni(O x H y )) has the best performance, showing 490.7mAcm at a potential of 1.45V -2 The current density is much higher than V W -Ni(O x H y )(316.1mA cm -2 ) and V S -Ni(O x H y )(203.3 mA cm -2 ), indicating that metal vacancies and oxygen vacancies synergistically enhance the catalytic performance of the catalyst for 5-hydroxymethylfurfural.

[0093] Figure 3 The nickel-based hydroxide / oxide (V W,S -Ni(O x H y )) The stability diagram of the catalyst, as shown in the figure, after 6 electrolysis at a potential of 1.45V, the 5-hydroxymethylfurfural (HMF) conversion rate and 2.5-furandicarboxylic acid (FDCA) Faraday efficiency were close to 100%, and it has excellent stability.

[0094] The above embodiments are provided only for the purpose of describing the present invention, and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. Various equivalent substitutions and modifications made without departing from the spirit and principles of the present invention should all be included within the scope of the present invention.

Claims

1. A method for preparing a nickel-based electrocatalyst rich in multi-vacancy defects, comprising: (1) dissolving the metal precursor and the anion precursor in 30 mL of ultrapure water respectively, and using an ultrasonic machine to disperse them for 30 min to obtain a first solution; (2) placing nickel foam in the first solution to obtain a second product; (3) placing the second product in a closed reactor lining for hydrothermal treatment, washing, and drying to obtain a third product; (4) soaking the third product in a hydrogen peroxide solution for 60 seconds, then washing and drying to obtain a metal-doped nickel-based catalyst precursor containing anion vacancies; (5) The metal-doped nickel-based catalyst precursor containing anion vacancies is electrochemically reconstructed in situ in an H-type cell containing 1 mol / L potassium hydroxide to obtain a nickel-based electrocatalyst rich in multiple vacancy defects.

2. The preparation method according to claim 1, wherein: The metal precursor in step (1) is selected from any one of sodium tungstate dihydrate, sodium molybdate dihydrate, sodium vanadate dodecahydrate, manganese nitrate tetrahydrate, cadmium nitrate nonahydrate, aluminum nitrate nonahydrate, and zinc nitrate hexahydrate; The anion precursor is selected from any one of sodium sulfide nonahydrate, sodium hypophosphite hydrate, and sodium borohydride; In the first solution, the molar ratio of anions to metal ions is 10:

1.

3. The preparation method according to claim 1, wherein: The nickel foam of step (2) further comprises the following treatments before use: The nickel foam was cut into 1cm*2cm blocks, and then ultrasonically treated with 3mol / L hydrochloric acid, ultrapure water, ethanol and ultrapure water for 15min in sequence, and finally placed in a vacuum oven and dried at 60°C for 12h.

4. The preparation method according to claim 1, wherein: The hydrothermal temperature of the hydrothermal treatment in step (3) is ≥160°C, and the hydrothermal time is ≥8h.

5. The preparation method according to claim 1, wherein: The washing in step (4) comprises: Ultrasonic washing was performed twice with ultrapure water and once with anhydrous ethanol, with each ultrasonic washing lasting 10 min. The drying condition is: drying at 60° C. for 12 h.

6. The preparation method according to claim 1, wherein: The electrochemical in-situ reconstruction in step (5) adopts a three-electrode system, comprising: Working electrode, reference electrode and counter electrode; wherein: The working electrode is a metal-doped nickel-based catalyst precursor containing anion vacancies, the reference electrode is mercury / mercuric oxide, and the counter electrode is a carbon rod; The electrochemical in-situ reconstruction conditions are: using cyclic voltammetry, in the potential range of 0.80V to 1.70V, at 50mV s -1 The scanning rate is more than 50 circles.

7. A nickel-based electrocatalyst rich in vacancy defects containing multiple vacancy defects prepared according to the preparation method according to any one of claims 1 to 6.

8. Use of the nickel-based electrocatalyst rich in multi-vacancy defects according to claim 7 in the electro-oxidation reaction process of 5-hydroxymethylfurfural.

9. The use according to claim 8, comprising: Weigh 63 mg of 5-hydroxymethylfurfural and dissolve it in the anode of an H-type cell containing 10 mL of potassium hydroxide solution, and the cathode also has 10 mL of potassium hydroxide solution; The catalytic performance was investigated by linear sweep voltammetry, electrolysis was performed by constant potential polarization, and the conversion of 5-hydroxymethylfurfural and the Faradaic efficiency of 2,5-furandicarboxylic acid were quantitatively determined by HPLC.

10. The use according to claim 9, wherein: The concentration of the potassium hydroxide solution is 1 mol / L; The potential interval of the linear sweep voltammetry method is 0.80V to 1.70V, and the potential of the constant potential polarization method is 1.45V.

Citation Information

Patent Citations

  • Nickel iron sulfide with in-situ conversion sulfur vacancies as well as preparation method and application of nickel iron sulfide

    CN111013607A

  • Preparation method of nickel-tungsten composite electrode and application of nickel-tungsten composite electrode in electrocatalytic oxidation

    CN114737215A

  • Preparation method and application of sulfur-doped nickel-cobalt-based catalyst for electrocatalytic oxidation of 5-hydroxymethylfurfural

    CN118292000A

  • Oxygen evolution catalyst as well as preparation method and application thereof

    CN118932403A

  • A catalyst for CO2 capture and conversion coupling with biomass oxidation, a preparation method therefor and an application thereof

    US20230191373A1